Appreciation and Criticism of the Monologue Play Script “Marsinah Menggugat” by Ratna Sarumpaet: A Feminist Perspective - Nurinsani, Jiwana; Yasmin, Kaila Azzahra; Sihite, Mutiara Angelica Hasian; Sipayung, Stephanie Br; Jiratullah, Huraiyah; Sinaga, Daniel Christian; Lubis, Fitriani (Lembaga Riset Mutiara Akbar, 2025)
This study aims to appreciate and critique the monologue drama script Marsinah Menggugat by Ratna Sarumpaet through a feminist perspective. The script tells the true story of a female laborer, Marsinah, who became a symbol of the struggle against injustice and oppression. This study uses a descriptive qualitative approach with a content analysis method to examine the drama text in depth. The focus of the analysis is directed at the representation of female characters, power relations, and expressions of resistance against patriarchal domination. The results show that Marsinah is depicted as a brave, critical woman with a high social awareness. The monologue in this script becomes a powerful medium to voice women's suffering and resistance against oppressive systems. The emotional dialogue and sharp narrative successfully convey social and feminist messages effectively. The conclusion of this study confirms that Marsinah Menggugat not only has literary aesthetic value, but also functions as a tool for social criticism that speaks out about gender injustice and fights for human justice.